Assessment of broiler chicken meat quality collected from different markets of Chittagong - Dey, JC; Jahan, I; Ghosh, S; Halder, BC; Ahmad, MH; Hossain, MA (Bangladesh Journal of Animal Science, 2020)
The study was conducted to assess the quality of broiler meat procured from four different markets of Chittagong city, (Baddar Hat; BH, Pahartoli; PHT, Jhaowtola; JT and Riazuddin bazar; RB). Broiler was collected from each of the market by replicating four times with five birds per replicate for assessing the meat quality in this study. A total of 20 shops was selected randomly and live broilers of similar age were collected from each shop located in the different places of metropolitan city of Chittagong to conduct the experiment. Meat samples were taken from the live broilers to appraise the quality based on the H2O level, pH, water holding capacity (WHC), extract release value (ERV), tyrosine value (TV) and thiobarbituric acid reactive substance value (TBARS) through the laboratory analyses. The data revealed that the TV and TBARS values differed significantly (P<0.01) between markets except for the other parameters (H2O, pH, WHC, ERV). The highest TV value (0.66) was found in the meat of PHT market while lowest TV value (0.54) being in BH and JT markets. The TBARS value was improved (P<0.01) in the meat of BH and JT markets compared to that of other markets. The road distance (RD) and the transporting time (TT) for carrying birds were affected (P<0.01) by markets. It can be concluded that the quality of broiler meat of different markets appears to be good based on the chemical evaluation, even though TT and RD might influence meat quality to a bit. Bang. J. Anim. Sci. 2020. 49 (1): 29-36